Identification of PLX4032‐resistance mechanisms and implications for novel RAF inhibitors. (6th January 2014) - Choi, Jaehyuk; Landrette, Sean F.; Wang, Tiffany; Evans, Perry; Bacchiocchi, Antonella; Bjornson, Robert; Cheng, Elaine; Stiegler, Amy L.; Gathiaka, Symon; Acevedo, Orlando; Boggon, Titus J.; Krauthammer, Michael; et al.
Summary BRAF inhibitors improve melanoma patient survival, but resistance invariably develops. Here we report the discovery of a novel BRAF mutation that confers resistance to PLX4032 employing whole‐exome sequencing of drug‐resistant BRAFV600K melanoma cells. We further describe a new screening approach, a genome‐wide piggyBac mutagenesis screen that revealed clinically relevant aberrations (N‐terminal BRAF truncations and CRAF overexpression). The novel BRAF mutation, a Leu505 to His substitution (BRAFL505H), is the first resistance‐conferring second‐site mutation identified in BRAF mutant cells. The mutation replaces a small nonpolar amino acid at the BRAF‐PLX4032 interface with a larger polar residue. Moreover, we show that BRAFL505H, found in human prostate cancer, is itself a MAPK‐activating, PLX4032‐resistant oncogenic mutation. Lastly, we demonstrate that the PLX4032‐resistant melanoma cells are sensitive to novel, next‐generation BRAF inhibitors, especially the 'paradox‐blocker' PLX8394, supporting its use in clinical trials for treatment of melanoma patients with BRAF‐mutations.